EQUIVALENT CHARACTERIZATION ON TRIEBEL-LIZORKIN SPACE - He, Cong; Chen, Jingchun; Fang, Houzhang; He, Huan (Matematichki Bilten, 2021)
In this paper, we give an equivalent characterization of TriebelLizorkin spaces. This reveals the equivalent relation between the mixed derivative norm and single variable norm. Complex interpolation and Littlewood-Paley decomposition are applied in our proofs.